(untitled) (Journal of Hama University, 2024)
The research aimed to identify the most common violations of administrators from the point of view of teachers in the schools of the first cycle of basic education, and the prevalence rates of these violations, their causes and ways to reduce them. The descriptive approach was used, and the questionnaire was used as a research tool applied to a sample of (81) teachers. The results showed that the most common violations are ignoring the delay and absence of some teachers (56.5%) of the respondents’ responses, and unfairness in cooperation with teachers and the distribution of work among them (39.5%). (29.5%) of teachers estimated that the failure of laws and regulations as a reason for administrators violating laws and regulations was between (26-50%.( The most important reasons for violations are due to the administrator’s desire to achieve a personal interest, the administrator’s desire to demonstrate his authority, and sympathy with humanitarian situations. While the most important ways to reduce violations were to improve the living conditions of workers in the educational field, and work to spread the culture of law and respect for it. Among the most important proposals is to spread a culture of respect for the rule of law, restore trust between teachers and administrators, and increase penalties for violators.